CANNING GREEN PEA VARIETIES OF VNIISSOK BREEDING - I. P. Kotlyar; E. P. Pronina; V. A. Ushakov; E. B. Blandinsky (Овощи России, 2012)
The conveyor of production of canning green pea varieties of VNIISSOK breeding is represented.